Parenting and Self-Criticism among Offspring: A Systematic Review - Shahzadi, Mafia; Khawar, Rabia; Habib, Shazia; Jabeen, Mehwish (Pakistan Journal of Humanities and Social Sciences, 2023)
Self-criticism involves negatively evaluating oneself and being critical of self-contemplations, beliefs, and actions, leading to dysfunction. Studies suggest that parenting plays a role in an individual's level of self-criticism. As primary caregivers, parents greatly influence their children's well-being, humility, distress, and self-criticism. To assess this relationship, a systematic review was conducted using various databases from 2003 to 2019. Out of 47 articles identified, 10 were excluded based on their abstracts and titles, and 23 were excluded after full-text assessment. The remaining 17 articles showed a significant association between parenting and self-criticism, with parental rejection being a stronger predictor of intense self-criticism. The systematic review identified limitations in the included studies' variables and outcomes, internal limitations, and a small number of research papers. To address these limitations, future studies should explore the relationship between parenting styles and self-criticism in different dimensions and investigate potential moderating factors such as environmental, psychological, and biological factors. Identifying such factors is crucial for developing effective prevention and intervention efforts to help adolescents manage their self-criticism and related mental health issues. In practical terms, the findings of the systematic review highlight the importance of parents, educators, and mental health professionals being mindful of how parenting styles may affect children's development of self-criticism. To reduce the risk of self-criticism and improve adolescents' emotional well-being, promoting positive parenting styles and behaviors, as well as identifying potential moderating factors, could be beneficial.